Teaching compassion through a community-led, experiential learning activity for undergraduate medical students: the Empathy Project - Lina Shoppoff; Christine Mathew; Kaite Burkholder Harris; Laura Muldoon; Sydney Persaud; Sophia Kelly-Langer; Elisha Davidson; Moira Alie; Carissa Grondin; Claire E Kendall (Canadian Medical Education Journal)
We co-facilitated a mandatory community-led experiential learning activity for medical students with the Alliance to End Homelessness Ottawa that demonstrates the feasibility and positive impact of incorporating community-led learning into the medical school curriculum.